Attachment Avoidance and Intimacy Decline: The Mediating Role of Expressive Suppression - Rodrigues da Silva, Diana; Wanjiku, Judith (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to examine the association between attachment avoidance and intimacy decline in romantic relationships and to test whether expressive suppression mediates this relationship among adults in Kenya.Methods and Materials: A descriptive correlational design was adopted with a sample of 391 adults recruited from different counties in Kenya, determined using the Morgan and Krejcie sample size table. Participants completed standardized self-report instruments: the Experiences in Close Relationships–Revised (ECR-R) for attachment avoidance, the Emotion Regulation Questionnaire (ERQ) for expressive suppression, and the Personal Assessment of Intimacy in Relationships (PAIR) Inventory for intimacy decline. Data analysis was conducted in two stages: bivariate relationships were tested using Pearson’s product–moment correlation coefficients in SPSS-27, and the hypothesized mediational model was examined using Structural Equation Modeling (SEM) with AMOS-21. Model fit was evaluated with multiple indices (χ²/df, GFI, AGFI, CFI, TLI, RMSEA).Findings: Attachment avoidance was strongly and positively associated with intimacy decline (r = .61, p < .001) and with expressive suppression (r = .54, p < .001). Expressive suppression was moderately correlated with intimacy decline (r = .48, p < .001). The SEM analysis showed excellent model fit (χ² = 112.47, df = 48, χ²/df = 2.34, CFI = .97, TLI = .96, GFI = .95, RMSEA = .058). Attachment avoidance had a significant direct effect on intimacy decline (β = .52, p < .001) and an additional indirect effect through expressive suppression (β = .16, p < .001), yielding a substantial total effect (β = .68, p < .001).Conclusion: These findings support attachment theory by confirming that expressive suppression functions as a key process linking avoidant relational orientations to intimacy erosion. The results highlight the importance of targeting emotional inhibition in interventions designed to maintain closeness and relational health across cultures.